Pharmacological mydriasis in patients with type 2 diabetes. A comparative study among different levels of diabetic retinopathy - Felipe Bekman Rocha; Nadyr Antonia Damasceno; Luziane Herzog de Azeredo Ramalho; Adroaldo de Alencar Costa Filho; Marcio Penha Morterá Rodrigues; Maria Luiza Gois da Fonseca; Raphael Boechat; Rubens Antunes da Cruz Filho; Eduardo de França Damasceno (Revista Brasileira de Oftalmologia)
ABSTRACT Objective: To analyze the diabetic autonomic neuropathy through the comparison between the pharmacological mydriasis in patients without diabetes and with type 2 diabetes. Methods: This is an observational, cross-sectional, case-control study. The patients were dilated with phenylephrine 10% and tropicamide 1% eye drops. They were divided into patients without diabetes mellitus (Control or Group Zero) and patients with type 2 diabetes mellitus (Case Group). These patients with diabetes were divided into six groups according to the international classification of diabetic retinopathy study (no diabetic retinopathy or Group 1; mild non- proliferative diabetic retinopathy or Group 2; moderate non-proliferative diabetic retinopathy or Group 3; severe non-proliferative diabetic retinopathy or Group 4; proliferative diabetic retinopathy without retinal laser photocoagulation or Group 5; and proliferative diabetic retinopathy with panretinal laser photocoagulation or Group 6). Each group included 20 patients. The main variable was the pupillary diameter after pharmacological dilation, and the secondary variables were gender, and age, and diabetic retinopathy stages. Vertical and horizontal pupillary diameter were measured. Analysis of variance test F, Student's t-test and Chi-squared were used for the statistical analysis. The statistical significance was defined as 0.05. Results: This study included 140 patients (280 eyes). The majority of the eyes had rounded pupil (240 of 280). The statistical analysis identified the smallest mean and standard deviation pupillary diameter in eyes with severe non-proliferative diabetic retinopathy (6.4 ± 0.53 mm, vertical, and 6.0 ± 0.84 mm, horizontal. Eyes with severe non-proliferative diabetic retinopathy (p = 0.00) and proliferative diabetic retinopathy treated with pan retinal photocoagulation (p=0.02) demonstrated statistical significance. When the group with no diabetes was compared with the group with diabetes, patients with no diabetes had a larger pupillary diameter (mean and standard deviation of 1.0 ± 0.2 mm) after pharmacologic mydriasis, mainly in patients with severe non-proliferative diabetic retinopathy. Conclusion: The diabetic autonomic neuropathy may influence pupillary pharmacological dilation in late stages of diabetic retinopathy, mainly in eyes with severe non-proliferative diabetic retinopathy.